Structure-function Studies of Cutinase - Wei Xia (Cutinase: Preparation and Application, 2021)
T. fusca cutinase has been cloned and expressed in Escherichia coli, which is capable of degrading not only plant cutin, but also a variety of soluble synthetic esters, and insoluble triglycerides. So far, there is no report about the crystal structure of T. fusca cutinase. Thus, in this study, high-quality crystals have been obtained from purified T. fusca cutinase protein for the first time and collected a set of reflection data at 1.54 Å. The final crystal structure was confirmed and obtained, whose R factor and free_R factor are 20.8% and 21.6% respectively. The catalytic center is shown as Ser130-His208-Asp176, the oxyanion hole is located at Try60-Met131, and the substrate site is occupied by H2O molecule. And then, structural comparison between T. fusca cutinase and other cutinase was also investigated. Based on structural analysis, the disulfide bond is the key core for the thermal stability of T. fusca cutinase. To investigate its contribution, cutinase mutant without disulfide bond (C241A/C259A) was constructed and expressed in Escherichia coli. The extracellular yield production of mutant decreased dramatically to 13.8%, and most was detected in cell as insoluble inclusion bodies. Its catalytic efficiency also decreased to 71.0%. Besides, CD spectra analysis showed that the secondary structure of mutant changed distinctly, which lead to reducing the thermal stability.